Pengembangan desa wisata sebagai destinasi wisata olahraga berbasis kearifan lokal untuk meningkatkan perekonomian masyarakat setempat. - Rabwan Satriawan; Ewan Irawan; Ainun Fitriani; Ermawan Santoso; Slamet Santoso (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
Bima Regency has not yet established a sports tourism village incorporating local wisdom. So, the study aims to develop village tours as tourist sports based on local wisdom to increase the public economy. Research is a type of research and development that uses the ADDIE development model. The sample for this study was Lambu Tourism Village, which was chosen for its potential scenic attractions. The study subjects consisted of two expert validators in sports tourism, two expert validators in general tourism, and visitors to the tourist site who served as trial respondents. This research instrument used a validation questionnaire given to expert validators and a feedback questionnaire to visitors to tourist attractions. The data analysis methods employed included quantitative descriptive analysis for assessing needs, expert validation of the product based on average scoring, and product feasibility testing measured by the percentage of community acceptance. The results of the validation of material experts from 2 validators, namely sports tourism attraction experts, validate sports tourism attractions, so the result is an average score of 89.5%, which shows that the sports tourism material is very feasible. Furthermore, expert validation is carried out with 2 validators, namely experts in the field of tourism, to validate sports tourism villages so that the validation results with an average score of 80.5% indicate that it is very feasible. So, this research is a novelty of a local wisdom-based sports tourism village that can improve the economy of local communities in Bima Regency.